Real-world practice patterns of eplerenone use for central serous chorioretinopathy - Ramesh Venkatesh; Vishma Prabhu; Aishwarya Joshi; Rubble Mangla; Rishi Singh; Lihteh Wu; Paolo Lanzetta; Baruch Kuppermann; Francesco Bandello; Francine Behar Cohen; Jay Chhablani (International Journal of Retina and Vitreous, 2023)
Abstract Purpose To report eplerenone use by retina specialists worldwide for central serous chorioretinopathy (CSCR). Methods A self-reporting questionnaire was distributed to retina specialists worldwide to gather clinicians’ perspectives on CSCR cases treated, eplerenone dosage and duration, reasons to use it, and side effects. Results The survey included 241 retina specialists (122 Indian and 119 international) with an average experience of 15.69 ± 9.59 years. Oral eplerenone was used to treat CSCR by 149 (62%) participants. Only 6% (n = 9) had easy access to verteporfin dye and photodynamic therapy. 30 (20%) of the 149 respondents changed their treatment with eplerenone after VICI trial results. Eplerenone was prescribed mostly for chronic CSCR (n = 86, 58%), regardless of involvement laterality. 62% (n = 92) had fewer than 25% CSCR cases treated with eplerenone. 85 (57%) respondents used eplerenone only when other treatments failed, while 36 (24%) used it as first-line treatment. 73 (49%) respondents, prescribed eplerenone at a 50 mg daily dose and 137 (92%) retina specialists used eplerenone for 0–3 months. The drug’s efficacy dissatisfied 21 (14%) study participants. 124 (83%) study participants did not encounter any ocular or systemic side effects with eplerenone use. Eplerenone related kidney and electrolyte issues were noted by 11 (7%) study participants. Conclusion The treatment of CSCR varies around the world and is primarily influenced by the photodynamic therapy availability and the findings of VICI trial. Despite the limited benefit of eplerenone reported by the VICI trial, it is still used as evidenced by real-world experience. Trial Registration Number Not applicable.